Inclisiran Usage in Very High-Risk Patients with Dyslipidemia Resistant to Statins and Ezetimibe Therapy - Marushko, Yevhen Yu.; Mankovsky, Georgiy B.; Levadska, Anastasiia A. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Background. Complications of systemic atherosclerosis (myocardial infarction, ischemic stroke) are the main causes of mortality and disability in the modern world. The relevance of this problem is determined by its scale: the number of deaths from cardiovascular disease has gradually increased from 12.1 million in 1990 to 18.6 million in 2019 and is on the rise. Today, the standard treatment regimen for dyslipidemia includes statins and ezetimibe. For patients who do not achieve the required lipid lowering, intensification of therapy with a relatively new group of drugs – PCSK9 inhibitors – is available. The aim. To study the effectiveness of inclisiran in the complex therapy of dyslipidemia in patients with very high cardiovascular risk. Materials and methods. The study design was a series of clinical cases, the data of which are described for comparison in dynamics. On the basis of the Department of Cardiometabolic Diseases of the Ukrainian Children’s Cardiac Center, a group of 7 patients with very high cardiovascular risk who did not achieve the target lipid parameters on standard therapy with rosuvastatin and ezetimibe was selected. Results. All the patients in the study group of very high cardiovascular risk with dyslipidemia resistant to standard combination treatment who took inclisiran as part of complex lipid-lowering therapy achieved a significant reduction in total cholesterol, but more importantly, they reached the target low-density lipoprotein cholesterol values. We did not find any side effects when using inclisiran. Conclusions. The present series of clinical cases demonstrates high efficacy of inclisiran as part of complex lipid-lowering therapy in patients with very high cardiovascular risk, who have a combination of coronary heart disease and type 2 diabetes mellitus. These results suggest the possibility of wider use of inclisiran in patients with very high cardiovascular risk to reduce cardiovascular morbidity and mortality.